Comparative estimation of diagnostic informativity of a fine-needle aspiration biopsy and pathomorphological investigation of nodal thyroidal tumors - A. F. Hummatov; S. A. Aliev; A. N. Abbasoc; A. K. Ismaylov; M. R. Huseynova (Клінічна хірургія)
Objective. Comparative estimation of diagnostic informativity of a fine-needle aspiration biopsy (FNAB) and pathohistological investigation of nodal thyroidal tumors.